Pelaporan Keberlanjutan : Standar dan Pengungkapan (Systematice Literature Review) - Santoso, Rizki Agung; Meuthia, Inten; Kartasari, Shelly Febriana (LPPM Universitas Trunojoyo Madura, 2025)
Sustainability reporting has garnered global attention in response to increasing demands for corporate accountability and transparency in environmental, social, and governance aspects. Although various reporting standards are available, their application and effectiveness in academic research still vary significantly. This study aims to examine the development of sustainability reporting literature, evaluate the dominant reporting standards used, and analyze the measurement methods employed in academic articles. A systematic literature review approach was applied to 30 selected articles published across five major databases: Emerald Insight, ScienceDirect, ResearchGate, SSRN, and DOAJ. The articles were thematically analyzed based on their objectives, the sustainability reporting standards adopted (e.g., GRI, SASB, IR, TCFD), analytical methods, and key findings. The results indicate that the Global Reporting Initiative (GRI) is the most commonly used standard, followed by a blended reporting approach. Most of the articles emphasize the importance of reporting quality, stakeholder engagement, and the integration of multiple frameworks. Commonly used methods include content analysis, panel data regression, and bibliometric analysis. In conclusion, sustainability reporting remains a growing area of research characterized by multidisciplinary approaches. The findings highlight the need for greater harmonization of reporting standards and more consistent measurement methodologies